Psychological Distress and Trends in Healthcare Expenditures and Outpatient Healthcare - Pirraglia, Paul A. (2011)
OBJECTIVES: To determine whether trends in psychological distress exist in the United States and whether trends in healthcare expenditures and outpatient visits were associated with psychological distress. STUDY DESIGN: Sequential cross-sectional study of nationally representative data. METHODS: We examined data from the National Health Interview Survey (NHIS) from 1997 to 2004 linked to 2 years of subsequent Medical Expenditure Panel Survey (MEPS) data. Psychological distress was measured in the NHIS using the K6, a 6-item scale of the Kessler Psychological Distress Scale, which we classified as no/low, mild-moderate, or severe. We examined subsequent annualized total, outpatient, and office-based expenditures, and outpatient and office-based visits from MEPS. RESULTS: Psychological distress remained stable from 1997 to 2004. There were upward trends in overall healthcare expenditures (P <.001) and outpatient expenditures (P <.001), but not outpatient visits. Overall healthcare expenditures, outpatient expenditures, and outpatient visits significantly increased as psychological distress increased from no/low to mild-moderate to severe. The interaction between psychological distress strata and year was not significant for expenditures or for visits. CONCLUSIONS: The upward trend in total and outpatient healthcare expenditures in the United States appears unrelated to psychological distress, although healthcare expenditures are consistently higher among those with greater psychological distress. Future work will explore the impact of treatment on costs and stability of the nation’s mental health over time.